ANALISIS PENGUKURAN KINERJA MENGGUNAKAN BALANCED SCORECARD PADA PERUSAHAAN DAERAH (STUDI KASUS PADA PDAM KABUPATEN BANYUMAS) - , TEGAR OKTA YOGANA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The era of global business competitive with the higher complexity requires all companies to be able to improve its performance in order to remain competitive. The orientation of the company that used to only focus on success measures of financial performance began to shift and expand their thinking on measures of non-financial performance. Using the Balanced Scorecard performance measurement initiated by Kaplan and Norton in 1992 is expected to address the needs of enterprise performance measurement in a more comprehensive and integrated. Successful implementation of the strategy is measured by the size of which is evident in a Balanced Scorecard. PDAM Kabupaten Banyumas as a profit-oriented companies should also start implementing a performance measurement system that is more comprehensive and integrated and able to measure the success of the implementation of any strategy chosen both financial performance and non-financial performance. Balanced Scorecard can be used as an effective tool for strategic management system and helps PDAM Kabupaten Banyumas be a strategy-focused organization.